Challenges and Opportunities of Supply Chain in Time of COVID-19 - Kovacevic, Rialda (World Bank, Washington, DC, 2021)
A supply chain is an essential building block of any health system. During the COVID-19 pandemic, supply chains have been forced to respond with unprecedented resilience, speed, and agility to cope with the situation at hand. Complete, end-to-end inventory visibility is vital to understand when vaccines, therapeutics, or diagnostics will be available for use. As one of the seven workstreams of Access to COVID-19 Tools Accelerator (ACT-A) Health Systems Connector (HSC), the supply chain workstream, and country counterparts share some insights and lessons learned.